Review: Isolation of Gelatin from Several Types of Fish - Suryaman, Ine Suharyani; Sulastri, Lela; Astuti, Enih Nindi; Delviyanti, Elis; Senja, Rima Yulia; Tomi, Tomi (Indonesian Journal of Pharmaceutics, 2025)
Indonesia is a country with the largest fishery waste, one of which is fish bones as a source of gelatin. Gelatin is the main protein that makes up skin and bone tissue in animals. This review was compiled to compare the results of isolating gelatin from bone waste in various types of fish. Articles were collected from the website https://scholar.google.co.id/ with "gelatin, gelatin content, gelatin in fish bones, viscosity, pH" in the 2015–2022 period, and 11 journals were obtained. In this literature study, a method for isolating gelatin from fish bone waste will be discussed, followed by an evaluation of the gelatin obtained, including its yield and its physical properties. It is hoped that the results of this review will provide information regarding a new source for gelatin isolation so that gelatin can be widely used by the food, pharmaceutical, cosmetic, and photographic industries, particularly in the pharmaceutical and food industries, which currently require gelatin as a stabilizer and emulsifier so that it can make and maintain the emulsion system.